The Study of LiDAR Technology in Improving the Construction Teams Productivity - Mohmad Fauzi, Norelya Ardyla; Zainal, Rozlin; Kasim, Narimah; Mohd Noh, Hamidun (Research in Management of Technology and Business, 2024)
In the new global economy, Malaysia recognizes the emergence of LiDAR in the market applied in various fields that can benefit users in management natural resources and become central issue for construction industry. The potential of LiDAR in Malaysian forestry is huge and knowledge and technology are required to process LiDAR data. However, other teams and construction businesses have never utilised LiDAR before, and in some cases, even those that are using the technology were not getting the most out of their survey data. Therefore, the objectives of this research were to study problems of LiDAR technology practice in construction team productivity, to study the solutions for LiDAR technology practice problem for construction team productivity and to evaluate the relationship between the main problems with the main solutions for LiDAR technology practice in construction team productivity. The research area was located in Johor Bahru. This study surveys covered 217 perceptions of Grade 7 contractors in Johor Bahru. The respondents were given a questionnaire by face-to-face meeting and in a link of google form through WhatsApp and Email. A total of 93 (43%) respondents have given feedback in the questionnaire. Descriptive statistic with frequency and crosstabs by SPSS software was used to analyse the data for all objectives. This research found that the main problem was lack of established standard and the main solutions such as be open to improve, combined with the appropriate software, remote operation from a third-person perspective and data can easily transfer recorded as the highest frequency. Meanwhile, the correlation between the main problems and main solutions with the strongest relationship was lack of long-term philosophy and planning with incorporate a system and a way of working that goes beyond the tools. This study may help G7 contractors adopt LiDAR technology to successfully complete construction projects and advance the Malaysian construction industry by improving construction team productivity.